Inferential trends towards error, scientific literacy and critical thinking: Pedagogical implications - Torres Bravo, Leyla (Opción, 2015)
In this paper I review the thesis set out by Thagard (2011) andÂ some of the ideas taken on again in Thagard and Nussbaum (2014) about Â the existence of bias or tendencies towards error in human inferential Â activities, which lead us to make mistakes and move us away fromÂ scientific knowledge. I will analyze their main proposals and, specifically,Â their implications on decision making and on scientific literacy throughÂ critical thinking. In particular, I will focus on the revision of motivatedÂ inference and inference driven by fear through which the intent is toÂ demonstrate the need for guiding us towards overcoming beliefs so, inÂ this way, we make correct decisions about what we must believe and doÂ in day-to-day and academic environments.